تحليل أثر أبعاد الولاء على العلامة التجارية دراسة تطبيقية لعينة من النساء المستخدمات للعلامة NIVEA في محافظة عجلون بالأردن: Analysis of the impact of loyalty dimensions on the brand an applied study of a sample of women who use the brand NIVEA in Ajloun governorate, Jordan - الفريح سلام; عطوات سلمى; طريف يمينة (Journal of North African Economies, 2025)
This study deals with brand loyalty, during a survey of the dimensions that constitute it. This is done according to a sample of women using the NIVEA brand, cosmetic product, circulating at the level of the city of Ajloun IN Jorden. To achieve this objective, we designed a questionnaire administered to a random sample of 60 people. In order to determine the degree of concordance and difference between them, bearing on its dimensions. Taking into account the demographic variables. The study aims at the impact of the most influenced dimensions. This is carried out by a statistics program (SPSS). Based on multiple regression analysis and other statistical methods. This study led to numerous results, the most important of which is to demonstrate the effect of factors (quality perceived،price،trust ،brand awareness) in NIVEA brand loyalty.